Two wrongs make a right - Liese, Chloe (Berkley Romance, 2022)
"There's much ado about everything when two adversaries become allies and fake a relationship to fool their meddling friends in this swoony, inclusive reimagining of the Bard's beloved play Much Ado About Nothing. Jamie and Bea have nothing in common except a meet-disaster and the mutual understanding that they couldn't be more wrong for each other. But when the people closest to them play Cupid and trick them into dating, Jamie and Bea realize they have something else in common after all-an undeniable need for revenge. Soon their plan is in place: 1. Fake date. Obnoxiously. Convince the meddlers they're madly in love. 2. Break up. Spectacularly. Dash everyone's hopes and put a stop to the matchmaking madness - once and for all. To convince everyone they've actually fallen for each other, Jamie and Bea will have to nail the performance of their lives. But as their final act nears and playing parts becomes easier than not, what once felt fake now seems all too real. What if Cupid's arrow wasn't so off the mark? And what if two wrongs do make a right?"--